Blockade of checkpoint ILT3/LILRB4/gp49B binding to fibronectin ameliorates autoimmune disease in BXSB/Yaa mice. (5th June 2021) - Su, Mei-Tzu; Inui, Masanori; Wong, Yi Li; Takahashi, Maika; Sugahara-Tobinai, Akiko; Ono, Karin; Miyamoto, Shotaro; Murakami, Keiichi; Itoh-Nakadai, Ari; Kezuka, Dai; Itoi, So; Endo, Shota; et al.
Abstract: The extracellular matrix (ECM) is the basis for virtually all cellular processes and is also related to tumor metastasis. Fibronectin (FN), a major ECM macromolecule expressed by different cell types and also present in plasma, consists of multiple functional modules that bind to ECM-associated, plasma, and cell-surface proteins such as integrins and FN itself, thus ensuring its cell-adhesive and modulatory role. Here we show that FN constitutes an immune checkpoint. Thus, FN was identified as a physiological ligand for a tumor/leukemia/lymphoma- as well as autoimmune-associated checkpoint, ILT3/LILRB4 (B4, CD85k). Human B4 and the murine ortholog, gp49B, bound FN with sub-micromolar affinities as assessed by bio-layer interferometry. The major B4-binding site in FN was located at the N-terminal 30-kDa module (FN30), which is apart from the major integrin-binding site present at the middle of the molecule. Blockade of B4–FN binding such as with B4 antibodies or a recombinant FN30-Fc fusion protein paradoxically ameliorated autoimmune disease in lupus-prone BXSB/ Yaa mice. The unexpected nature of the B4–FN checkpoint in autoimmunity is discussed, referring to its potential role in tumor immunity. Abstract : Fibronectin functions as an immune checkpoint molecule